دور المضامين الثقافية في ترسيخ الهوية الجزائرية - سعدون، فاطمة (جامعة منتوري قسنطينة - كلية الآداب واللغات - قسم اللغة العربية وآدابها, 2017)
تعد الثقافة مجموعة العادات والتقاليد والقيم المشتركة والخصائص التي تجمع مجموعة من الأفراد، وهي نسق اجتماعي عام يتفاعل مع أنساق فرعية، مما يجعلها متغيرة قابلة للتعديل زمانيا ومكانيا، فهي إذن وعي الذات وتفاعلها في حيز المتغيرات الاجتماعية والإنسانية، ولعل هذا ما يجعل الثقافة مرتبطة بالهوية، ذلك أن الهوية هي مجموعة الخصائص التي يمكن للفرد من خلالها أن يعرف نفسه في علاقته بالمجموعة الاجتماعية التي ينتمي إليها، ويتميز عن باقي الأفراد في المجموعات الاجتماعية الأخرى، فهي تلك السمة المنغرسة في الذات والمميزة لها في الآن ذاته، ولئن كانت الثقافة والهوية ميزتان أساسيتان للفرد، وصورة عن وعي الذات في مواجهة التغييرات الطارئة على العالم في ظل العولمة، فكيف أسهمت المضامين الثقافية في ترسيخ الهوية الجزائرية؟ وهل يمكن الحديث عن خصوصية لهذه الهوية في مواجهة التحديات الاجتماعية والثقافية المرتبطة بعالم يسعى إلى دحض الخصوصيات وترسيخ مبدأ العولمة؟. Culture is a set of customs, traditions, shared values and characteristics that bring together a group of individuals. It is a general social context that interacts with sub-patterns, making them temporally and spatially changeable, so it is self-awareness and interaction in the space of social and human variables. Perhaps this makes culture associated with identity, since identity is the set of characteristics through which an individual can identify himself in his/ her relationship of the social group to which he belongs and is distinguished from the rest of the people in other social groups. It is that self-centered and distinctive trait. At the same time, while culture and identity are fundamental characteristics of the individual and a form of self-awareness in the face of changes to the world under globalization, how did the cultural implications contribute to the consolidation of Algerian identity? Is it possible to talk about the specificity of this identity in the face of social and cultural challenges associated with a world that seeks to refute the specifics and establish the principle of globalization?
Keywords: التنوع الثقافي -- الهوية الثقافية -- المجتمع الجزائري -- المضامين الثقافية -- العولمة الثقافية